Digital communications - Glover, Ian, 1959-; Grant, Peter M. (Harlow, England ; New York : Prentice Hall, 2010)
'Digital techniques are central to almost all modern telecommunications systems. The third edition of Digital Communications has retained both its comprehensive coverage and its balance between theory, applications and systems implementation. Its main aim is to develop the mathematical theory of signal processing and use this theory to describe modern digital communications.''This text is suitable for undergraduates and first year postgraduate students. It also provides an excellent overview for professional engineers.'--BOOK JACKET.
Includes bibliographical references and index.
Includes Web resources.
Keywords: Digital communications